Comparative efficacy of intralesional placental extract and intralesional triamcinolone acetonide in the management of OSMF - Christopher V Shinde; Nisheeth Saawarn; Sahil Kohli; Pooja Khare; Ajita Singh; Krishna M Sagar (Wolters Kluwer Medknow Publications, 2019)
Context: Oral submucous fibrosis (OSMF) is characterized by excessive collagen production in the submucosa leading to progressive fibrosis of the oral mucosa and atrophic changes of the epithelium. Aim: To clinically evaluate the efficacy of intralesional injections of placental extract (2ml) in comparison to intralesional injections of triamcinolone acetonide (40mg/ml; 1ml) in the management of OSMF patients. Methodology: This randomized, parallel-group, single-blinded outcome-based study, consisted of 40 diagnosed cases of OSMF. The patients were divided into two groups of 20 each in placental extract group and triamcinolone acetonide group. Patients were administered test medications weekly in respective groups by intralesional mode for a period of 10 weeks. Parameters taken into consideration and compared weekly were burning sensation, pain, mouth opening, tongue protrusion, and cheek flexibility. Result: The data so obtained was tabulated and subjected to statistical analysis using Chi-square test, Mann-Whitney test, Wilcoxon ranked test, and t-test by means of SPSS version 20 software to reach conclusive results. There was significant improvement in burning sensation, pain, mouth opening, tongue protrusion, and cheek flexibility in both groups. Better and faster improvement in tongue protrusion and cheek flexibility was achieved in triamcinolone group as against placental extract group. Conclusion: The intralesional triamcinolone acetonide was found to be a superior intralesional drug in comparison to placental extract.